The Impact Of FDI On Economic Growth In South Africa: Does The Sector Matter? - Keleme, Mamontshi (Graduate School of Business (GSB), 2024)
Foreign Direct Investment (FDI) is crucial for wealth-creating economic growth. Conceptually, FDI could bridge the investment gap and raise much-needed revenue for South Africa's financial requirements. However, much of the existing evidence on the effects of FDI on economic growth is at the macro level, with scant attention focused on the impact of FDI on economic growth at sector levels in South Africa. Consequently, this study aimed to examine the impact of agricultural, manufacturing, mining, construction, finance, and transport FDI on economic growth for the period 1993 to 2019 in South Africa. The study used panel data to estimate the relationship between the FDI-to-GDP ratio and economic growth. The Panel ARDL results revealed that the effect of sectoral FDI on national GDP was positive but insignificant in the long- and short-run. In addition, the results revealed that domestic investment had a negative and significant effect on growth in the long and short run, at 5% and 10% significant levels, respectively. In line with previous studies, all other variables, such as human capital, trade openness, and total consumption expenditure, had excepted signs in the short run. However, all variables were statistically significant in the long run and had unexpected signs. The short-run PMG result shows that FDI inflows into the construction, mining, and transport sectors had a significant positive relationship with the economic growth rate. In contrast, the FDI inflow in the agriculture, finance and manufacturing sectors had a significant negative relationship with economic growth.